Correction to: Comparison of 2D vena contracta area with 3D planimetric mitral valve area in rheumatoid mitral valve disease - Gök, Gülay; Sayar, Nurten; Kuru Öz, Didem; Erer, Hatice Betül; Ekmekçi, Ahmet; Eren, Mehmet (Springer, 2020)
In the original publication of the article one co-author, A. Zencirci, was listed by mistake. Dr. A. Zencirci has not contributed to this article and therefore, the author list has been updated. The author name A. Zencirci has been removed. All authors have agreed to the updated author list. Correct order given in this article. The original article has been corrected.
Orijinal makaledeki bir hatadan kaynaklanan düzeltme.
Keywords: 3D-Echocardiography; Mitral Stenosis; Transesophageal Echocardiogrpahy